Burnout syndrome and associated factors among healthcare workers in COVID-19 contact tracing teams: A cross-sectional study from Türkiye - Çoban, Ali; Nazlıcan, Ersin; Yüzügüllü, Didem; Demirhindi, Hakan (Scientific Reports in Medicine, 2026)
Objective: The aim of this study is to investigate levels of occupational burnout, anxiety, and quality of life among healthcare workers engaged in contact tracing activities during the pandemic.Methods: This cross-sectional study was conducted in a provincial center in southern Türkiye. Between September 2021 and April 2022, 210 healthcare professionals actively serving in contact tracing teams were recruited into the study. Participants were given a questionnaire covering sociodemographic information, the Maslach Burnout Inventory, and the Health Workers' Work-Life Quality Scale. Inferential analyses included the chi-square test, Student's t-test, Mann–Whitney U test, one-way ANOVA, the Kruskal–Wallis test and linear regression analysis.Results: The mean age of the 210 participants was 39.8 years and 73.8% were female and 26.2% were male. Physicians reported lower quality-of-life scores than others. Men exhibited higher scores on the depersonalization subscale than women. Physicians and dentists scored higher on the depersonalization subscale than other occupational groups. Professionals who lived outside their homes during the contact tracing period had higher anxiety, emotional exhaustion, and depersonalization scores, as well as lower personal accomplishment scores, than those who lived at home. Healthcare professionals assigned to swab collection duties reported higher emotional exhaustion and depersonalization scores than those not performing such tasks.Conclusions: Of all the professional groups studied, physicians exhibited the highest burnout levels and the lowest quality-of-life scores. Additionally, healthcare professionals assigned to swab collection duties demonstrated significantly higher burnout levels. These results highlight the urgent need for targeted psychosocial support, workload management, and protective interventions.
Keywords: COVID-19; Pandemics; Health Personnel; Burnout; Anxiety; Quality of Life